Risk compensation behaviours in construction workers’ activities - Feng, Y.; Wu, Peng (Taylor and Francis Ltd., 2015)
The purpose of this study was to test whether the construction workers have the tendency of engaging in risk compensation behaviours, and identify the demographic variables, which may influence the extent to which the construction workers may show risk compensation behaviours. Both quantitative (survey) and qualitative (interviews) approaches were used in this study. A questionnaire survey was conducted with all the construction workers on three building construction sites of a leading construction company in Australia. Semi-structured interviews were then conducted to validate the findings of the quantitative research. The findings indicate that workers tend to show risk compensation behaviours in the construction environment. The workers with more working experience, higher education, or having never been injured at work before have a higher tendency to show risk compensation in their activities than the others. The implication is that contractors need to assess the potential influence of workers’ risk compensation behaviours when evaluating the effect of risk control measures. It is recommended that supervisors pay more attention to the behavioural changes of those workers who have more experience, higher education, and have never been injured before after the implementation of new safety control measures on construction site.